Efektivitas Implementasi Perencaan Anggaran Melalui Realisasi terhadap Kinerja Keuangan Palang Merah Indonesia Kota Tangerang Selatan - Sandi Yuda Wardani; Sri Retnaning S; Zulfitra Zulfitra (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine and analyze the effectiveness of budget planning implementation and realization on the financial performance of the Indonesian Red Cross in South Tangerang City. This study was designed using quantitative methods. The study population consisted of 123 permanent employees. The sampling process used a saturated sampling method, resulting in a sample of 123 respondents. The research data was further processed using Smart PLS 4.0. The analytical method used was SEM PLS. With a T-statistic value of 8.956, much greater than 1.96, and a P-value of 0.000, much smaller than 0.05, it shows that budget planning has a positive and very significant effect on budget realization. The T-statistic value is far above 1.96 and the P-value is 0.000, which shows that budget realization has a positive and significant effect on financial performance. The study concluded that Budget Planning has a significant positive effect on Financial Performance at the Indonesian Red Cross in South Tangerang City. Budget Planning has a significant positive effect on Budget Realization at the Indonesian Red Cross in South Tangerang City. Budget Realization has a significant positive effect on Financial Performance at the Indonesian Red Cross in South Tangerang City.